2022
DOI: 10.1097/md.0000000000029294
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and prognostic significance of the SET-CAN/NUP214 fusion gene in hematological malignancies: A systematic review

Abstract: Background: The SET-CAN/NUP214 fusion gene resulting from chromosomal del(9)(q34.11q34.13) or t(9;9) (q34;q34) has been found in T-cell acute lymphoblastic leukemia (T-ALL), B-cell acute lymphoblastic leukemia (B-ALL), acute myeloid leukemia (AML) and myeloid sarcoma (MS). Furthermore, the SET-CAN/NUP214 fusion gene has been found in the T-ALL cell line LOUCY and the AML line MEGAL. The common features of these cases are insensitivity to chemotherapy and poor prognosis. We reviewed the characteristics and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The overall frequency of NUP214 rearrangements was 2.08%; notably, the frequency was significantly higher in T-ALL (23.53%) than in AML (1.64%). Previous studies have reported frequencies of 6% for SET::NUP214 [ 18 ] and up to 6% for NUP214::ABL1 in T-ALL cases [ 12 ]. Collectively, these figures amount to 12%, which is approximately half the frequency found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall frequency of NUP214 rearrangements was 2.08%; notably, the frequency was significantly higher in T-ALL (23.53%) than in AML (1.64%). Previous studies have reported frequencies of 6% for SET::NUP214 [ 18 ] and up to 6% for NUP214::ABL1 in T-ALL cases [ 12 ]. Collectively, these figures amount to 12%, which is approximately half the frequency found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in the other fusion proteins, the NUP214 portion in the NUP214-ABL1 fusion protein is incorporated into the NPC, thereby combining the ABL1 tyrosine kinases to ensure that they can cross-phosphorylate and thus activate each other [ 17 ]. Regardless of the NUP214 partner gene or disease type, a common characteristic of all NUP214 rearrangements is that they are associated with treatment resistance and poor prognosis [ 18 , 19 ]. However, numerous studies in mice have shown that NUP214 rearrangements alone are insufficient for or at least inefficient in leukemogenesis [ 17 , 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the collected patient information, the highest WBC count was 604.4 × 10 9 /L (T-ALL) and this patient died 5 months after diagnosis. The median percentage of leukemic blasts in the bone marrow was high (82.0-97.0%), probably reflecting the high proliferation status of fusion gene positive patients ( 4 , 24 ).…”
Section: General Features Of the Patientmentioning
confidence: 99%
“…There is a large difference in the age of patients at initial diagnosis, the youngest patient is only 8 years old (T-ALL), the oldest patient is 58 years old (T-ALL), the average age is 30.2 years old and the patients are distributed in all age groups ( 6 , 17 , 24 , 26 , 35 , 41 ). Relatively speaking, the probability of fusion gene positive in adult leukemia patients is higher ( 40 ).…”
Section: General Features Of the Patientmentioning
confidence: 99%
See 1 more Smart Citation